Physical Activity in Pregnancy: A Preventive Measure Against Postpartum Depression - Sadowski, Jakub; Dołęga, Julia; Zabawa, Bartłomiej; Łabuś, Małgorzata; Krzykawski, Karol; Papież, Łukasz; Maciejczyk, Tomasz; Sieńko, Antoni; Hudzińska, Patrycja; Mól, Piotr (Quality in Sport, 2024)
Introduction: The aim of this study is to present current knowledge on the role of physical activity during pregnancy in reducing postpartum depression (PPD) symptoms. PPD is a widespread mental health condition, which significantly impacts maternal and neonatal well-being. Exercises during pregnancy are recognized as a preventative strategy that promotes both physical and mental health, benefiting mothers and their children. Materials and Methods: The study involved a systematic review of the literature using databases such as PubMed, NCBI, and Google Scholar. Key terms included "postpartum depression", "physical activity", “baby blues” and "mental health." Articles without full-text access were excluded. State of Knowledge: Postpartum depression affects up to 15% of women, while baby blues impact around 80% shortly after childbirth. Physical activity improves emotional health by alleviating stress, anxiety, and depressive symptoms. Evidence highlights that regular, moderate exercise during pregnancy can significantly reduce the risk of PPD, particularly in women with high-risk factors such as obesity or a history of mental health disorders. Mechanisms include hormonal regulation, endorphin release, and reduced inflammation. While light to moderate activities like walking, swimming, or yoga are beneficial, high-intensity exercise may pose risks and should be approached with caution. Conclusions: Physical activity during pregnancy is a non-pharmacological intervention, which mitigate PPD risks. Tailored, safe exercise routines, improve mental resilience and overall health in pregnant mothers. Further research is needed to refine exercise recommendations based on individual health profiles.